The Influence of Digital Literacy, Digital Behavior, and Perceived Usefulness on Green Finance Awareness through Green Behavioral Intention in the Multifinance Context of Indonesia. - Handy Kassapa; Iriene Anugrah Susanti; Diena Dwidienawati (Eduvest - Journal of Universal Studies, 2026)
This study examines the influence of digital literacy, digital behavior, and perceived usefulness on green finance awareness, with green behavioral intention acting as a mediating variable within Indonesia’s multifinance sector. As sustainable finance initiatives expand under regulatory encouragement, awareness among financial employees remains uneven, particularly in emerging markets where digital readiness varies. Drawing upon the Technology Acceptance Model and the Theory of Planned Behavior, this research adopts a quantitative explanatory approach using survey data collected from 270 employees of multifinance institutions in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate direct and indirect relationships among constructs. The findings reveal that digital literacy, digital behavior, and perceived usefulness significantly influence green behavioral intention, which in turn exerts a strong positive effect on green finance awareness. Although the direct effects of digital factors on awareness remain significant, their impacts are partially mediated by green behavioral intention. These results highlight the importance of strengthening digital competencies and fostering pro-environmental behavioral intentions to enhance sustainable finance awareness. The study contributes to the integration of digital transformation and sustainability frameworks while offering practical implications for regulators and multifinance institutions seeking to accelerate green finance adoption in Indonesia